Effect of composted plant based and animal derived materials on Chinese kale (Brassica oleracea var. alboglabra) performance in raised beds. - Somniyam, P.; Pupakdeepan, W.; Phatdiphanpreeda, P.; Somniyam, V. (International Journal of Agricultural Technology, 2025)
The application of organic planting materials influenced the physicochemical properties of growing media and significantly affected the growth and yield of Chinese kale cultivated in raised beds. Composted animal manures, particularly porcine and poultry manure, provided higher nitrogen and phosphorus levels, enhancing vegetative growth. Among the plant-based materials, rain tree leaves contained the highest nitrogen content; however, high nitrogen alone did not guarantee optimal growth, emphasizing the importance of nutrient balance and physical media structure. Rice husk biochar improved porosity, bulk density, and water-holding capacity, yet failed to achieve the highest yield when applied alone. The combination of filter cake or old mushroom lumps with porcine manure led to superior plant height, stem diameter, canopy width, leaf number, and leaf size. These treatments also showed higher leaf greenness, highest fresh and dry biomass, and lower root-to-shoot ratios, reflecting efficient biomass allocation toward harvestable parts. Although plant-based and animal-based materials showed significant individual effects, their interaction was not statistically significant, suggesting additive rather than synergistic effects. The superior performance of magnesium-rich materials such as filter cake highlighted the role of magnesium in chlorophyll synthesis and leaf development. Overall, integrating nutrient-dense animal manures with structurally beneficial plant-based materials improved the fertility and physical quality of growing media, resulting in enhanced growth and yield of Chinese kale. These findings demonstrated the potential of locally available organic resources, particularly combinations of porcine manure with filter cake or mushroom waste, as viable alternatives to chemical fertilizers for sustainable leafy vegetable production in raised bed systems.